2020
DOI: 10.1200/jco.2020.38.15_suppl.8032
|View full text |Cite
|
Sign up to set email alerts
|

Frontline brentuximab vedotin as monotherapy or in combination for older Hodgkin lymphoma patients.

Abstract: 8032 Background: Older patients with classical Hodgkin lymphoma (cHL) have poor outcomes relative to younger patients, often due to comorbidities and toxicities related to standard first-line (1L) chemotherapy (5-yr PFS: 30%–45% vs 75%–80%) (Evens 2008; Proctor 2009). Brentuximab vedotin (BV, ADCETRIS®), a CD30-directed antibody-drug conjugate, has robust activity in patients refractory to several lines of chemotherapy. Methods: This phase 2, open-label study, SGN35-015 (NCT01716806), evaluated efficacy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…BV is an antibody drug conjugate targeting CD 30 that has shown promising single-agent activity in relapsed/refractory HL [ 11 , 12 ]. Also, frontline BV monotherapy in elderly patients has yielded outstanding results with an ORR of 92% and median OS of 77.5 months [ 13 ]. Friedberg et al reported a phase 2 nonrandomized study of BV plus dacarbazine in newly diagnosed classical HL patients older than 60 years (n = 22) ineligible for cytotoxic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…BV is an antibody drug conjugate targeting CD 30 that has shown promising single-agent activity in relapsed/refractory HL [ 11 , 12 ]. Also, frontline BV monotherapy in elderly patients has yielded outstanding results with an ORR of 92% and median OS of 77.5 months [ 13 ]. Friedberg et al reported a phase 2 nonrandomized study of BV plus dacarbazine in newly diagnosed classical HL patients older than 60 years (n = 22) ineligible for cytotoxic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another trial assessed the BV-Nivo combination in 21 patients. After a median follow-up of 26.2 months, the ORR was 95% and the median PFS was not reached [30]. For more fragile, unfit, elderly patients, BV alone or in combination with dacarbazine may also represent well-tolerated and beneficial approaches [30,31].…”
Section: Novel Reduced-toxicity Approaches For Elderly Patientsmentioning
confidence: 99%
“…Первые сообщения об успешном применении брентуксимаба ведотина в 1-й линии терапии в монорежиме или в сочетании с химиопрепаратами и иммунотерапией у пациентов с кЛХ старшей возрастной группы сделаны более 5 лет тому назад. В декабре 2020 г. на 62-й конференции ASH C. Yasenchak привел результаты анализа выживаемости больных старше 60 лет, получавших BV в монорежиме или в сочетании с дакарбазином, или бендамустином, или ниволумабом [5]. На рис.…”
unclassified
“…Режимы применения брентуксимаба ведотина в монорежиме и в комбинации с химиопрепаратами и иммунотерапией у пациентов с кЛХ в старшей возрастной группе (адаптировано[5]). The regimen of brentuximab vedotin application as alone or in combination with chemotherapy and immunotherapy in patients with cHL of an elderly section (adapted from[5]). …”
unclassified
See 1 more Smart Citation